INTERNET SECURITY DESIGN ON WIFI NETWORKS USING VIRTUAL PRIVATE NETWORK - Pangaribuan, Rismawati; Hidayatullah, Hidayatullah (JURNAL TEKNISI, 2025)
Abstract : The rapid development of internet technology has increased the need for secure data transmission, especially when using public WiFi networks that are highly vulnerable to threats such as account tapping, data theft, and unauthorized access. This research aims to design a secure internet system using a Virtual Private Network (VPN) on a WiFi network at the Bireuen Technology Innovation Store. The proposed solution involves implementing a VPN system that ensures encrypted and secure communication between clients and servers. The study employs a multi-stage method: data collection, system analysis, design, implementation, and testing. The system was developed using the Ubuntu 14.04 (32-bit) operating system and OpenVPN software. Testing results show that the VPN successfully encrypts user data and secures communication channels from public WiFi to the VPS server. This proves that VPN implementation is an effective solution to enhance internet security in public network environments. The study concludes that a VPN system is essential for protecting data transmission and user privacy, especially in unsecured wireless networks.Keywords: security; ubuntu 14.04 (32 bit); VPN. Abstrak: Perkembangan teknologi internet yang pesat telah meningkatkan kebutuhan akan transmisi data yang aman, terutama saat menggunakan jaringan WiFi publik yang sangat rentan terhadap ancaman seperti penyadapan akun, pencurian data, dan akses tidak sah. Penelitian ini bertujuan untuk merancang sistem internet yang aman menggunakan Virtual Private Network (VPN) pada jaringan WiFi di Toko Inovasi Teknologi Bireuen. Solusi yang diusulkan melibatkan penerapan sistem VPN yang memastikan komunikasi terenkripsi dan aman antara klien dan server. Penelitian ini menggunakan metode multi-tahap: pengumpulan data, analisis sistem, perancangan, implementasi, dan pengujian. Sistem ini dikembangkan menggunakan sistem operasi Ubuntu 14.04 (32-bit) dan perangkat lunak OpenVPN. Hasil pengujian menunjukkan bahwa VPN berhasil mengenkripsi data pengguna dan mengamankan saluran komunikasi dari WiFi publik ke server VPS. Hal ini membuktikan bahwa implementasi VPN merupakan solusi yang efektif untuk meningkatkan keamanan internet di lingkungan jaringan publik. Penelitian ini menyimpulkan bahwa sistem VPN sangat penting untuk melindungi transmisi data dan privasi pengguna, terutama dalam jaringan nirkabel yang tidak aman.Keywords: keamanan; ubuntu 14.04 (32 bit); VPN.